PEMILIHAN PERUMAHAN TERFAVORIT MENGGUNAKAN METODE VIKOR DAN TOPSIS DENGAN GUI MATLAB (Studi Kasus: Perumahan Mijen Semarang) - Alika Ramadhani; Rukun Santoso; Rita Rahmawati (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2019)
The increase in the population of Semarang has an impact on the increasing demand for residential housing. Unfortunately, the limitations of the area became an obstacle in Semarang to develop residential areas. This development of residential housing in Semarang leads to suburban such as Mijen. The method that can be used to choose favorite housing is Visekriterijumsko Kompromisno Rangiranje (VIKOR) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Both methods can be applied to solve Multiple Criteria Decision Making (MCDM) issue. This study has 8 alternatives of residential housing in Mijen with 5 criteria such as Price, Payment Method, Building Specifications, Housing Facilities, and Location. This research was design with Graphical User Interface (GUI) Matrix Laboratory (MATLAB) as computing tool. VIKOR and TOPSIS method on this research, obtained the same result that the most favorite residential housing is A5. Keywords: Housing, SPK, VIKOR, TOPSIS, GUI